To kill or not to kill: a question to yeast and bacteria - Araújo, Rita da Conceição Carvalho (2019)
Since the first discovery of penicillin by Alexander Fleming, antibiotic resistance has been reported in several species of microorganisms. Nowadays, the misapplication and overuse of antibiotics in clinical and farming settings, associated with the lack of new drugs discovery, resulted in a rapid rise and spread of bacterial agents resistant to not one, but several commercially available antibiotics. With this been said, an effective solution must arise to tackle this emerging and yet unsolved problem. Due to their antagonistic ability to produce killer toxins (KT), yeasts can offer a possible solution to combat clinically/industrially relevant bacteria. Therefore, the present work aims to evaluate the killer potential of several yeast species against six different bacteria: Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, all members of the ESCAPE group with high prevalent pathogenicity and antibiotic resistance, and Salmonella typhimurium and Bacillus subtilis that are clinically/industrially resistant bacteria and food contaminants. Hence, a library of 255 yeasts from different sources was screened for antibacterial activity. From these, 49 demonstrated to exert an antibacterial effect against the selected bacteria and, from these, two were selected as the most promising namely, Saccharomyces cerevisiae L680 and Hanseniaspora uvarum TB264. Subsequently, the selected yeasts were incubated as monocultures and in co-cultures with different yeast:bacteria ratios, aiming at the production and initial characterization of potential killer toxins. The supernatants from the (co)cultures were collected, concentrated and tested for antibacterial activity. In this regard, the concentrated supernatant extracts from L680 demonstrated to be effective against all of the selected bacteria, presenting a stronger antibacterial activity than the TB264 supernatant. Simultaneously, the supernatants were analyzed by SDS-PAGE and Native-PAGE to assess the presence of protein bands that could be addressed for killer activity. The present work provides cues for the production of new yeast-derived antimicrobial agents. Moreover, the antibacterial activity reported in this work reveals the promising application of KTs for the combat against resistant bacteria.